Cost-effectiveness of ramucirumab plus paclitaxel as maintenance therapy for patients with advanced HER2-negative gastric or gastroesophageal junction cancer - Li, Dong; Zhao, Xue; Jia, Huixian; Cui, Rong; Cao, Afang; Huo, Liman (Frontiers in Oncology, 2026)
ObjectiveThis study a to evaluate the cost-effectiveness of ramucirumab plus paclitaxel as a switch maintenance therapy for patients with advanced HER2-negative gastric or gastroesophageal junction cancer, from the perspective of the Chinese healthcare system, to guide clinical decision-making and reimbursement policies.MethodsA three-state Markov model (progression-free, progressed disease, and death) was developed based on data from the ARMANI phase III randomized controlled trial. Two treatment strategies were compared: ramucirumab plus paclitaxel versus continuation of oxaliplatin-based chemotherapy (FOLFOX/CAPOX). Cost data were obtained from national procurement platforms and published literature; utility values were derived from EQ-5D instruments. A willingness-to-pay (WTP) was set at three times China’s 2024 per capita GDP, equivalent to USD 40, 457.32 per QALY.Base-case analysis, one-way and probabilistic sensitivity analyses, threshold price analysis, and a patient assistance program (PAP) scenario were conducted.ResultsThe base-case analysis yielded an incremental cost-effectiveness ratio (ICER) of USD 138, 320.14/QALY, which exceeded the WTP threshold. Under the PAP scenario (i.e., “buy two, get one free”), the ICER was reduced to USD 95, 304.89/QALY, but remained above the threshold. Sensitivity analyses showed the model was most sensitive to utility values, discount rates, and drug price. Threshold analysis suggested that the price of ramucirumab would need to be reduced to approximately 24% of its current level (~USD 149/100mg) to achieve cost-effectiveness; even under the PAP scenario, a further price cut to 36% (~USD 223/100 mg) would still be required.ConclusionAt current pricing and under the existing PAP framework, ramucirumab plus paclitaxel is not a cost-effective switch maintenance strategy in advanced HER2-negative gastric or gastroesophageal junction cancer in China. Significant price reductions through national negotiations may enable this regimen to become economically viable within the Chinese healthcare system.